2009
DOI: 10.1089/end.2008.0668
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Displacement for CT-Guided Tumor Radiofrequency Ablation: Techniques and Anatomic Considerations

Abstract: Lower pole, posterior renal lesions are more likely to necessitate bowel displacement. Bowel displacement techniques are effective and safe in displacing bowel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Percutaneous hydro/ gas dissection is a simple and very effective technique and should be part of the routine armamentarium of any ablation practice [55][56][57]. Consensus level: strong As size, number and location are all important features, there is a strong consensus that these three factors should be considered in concert when evaluating the appropriateness of ablation in any given patient.…”
Section: Proximity To Vulnerable Structuresmentioning
confidence: 99%
“…Percutaneous hydro/ gas dissection is a simple and very effective technique and should be part of the routine armamentarium of any ablation practice [55][56][57]. Consensus level: strong As size, number and location are all important features, there is a strong consensus that these three factors should be considered in concert when evaluating the appropriateness of ablation in any given patient.…”
Section: Proximity To Vulnerable Structuresmentioning
confidence: 99%
“…However, despite refinements in ablation technology, a limitation in liver ablation is adjacent thermal injury when the target lesion is along the surface of the liver as demonstrated in these patients. Strategies have emerged to protect the surrounding tissues including fluid or gas displacement, balloon interposition, thermometry, and torqueing of tissue (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up contrastenhanced MRI (f) of the mass after ablation (arrow) demonstrates complete devascularization of the mass without injury to adjacent structure. that the instillation of fluid separated the liver from the gastrointestinal tract in 78% of cases (4,5). Most recently, reports have emerged using a hyaluronic acid gel in humans and thermoprotective gels in an animal model (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors applied injection of normal air [44], while others reported the use of carbon dioxide (CO2) for organ displacement [45, 46]. CO2 seems to be particularly useful, as it is quickly reabsorbed by the body and eliminated by respiration.…”
Section: Gas Insufflationmentioning
confidence: 99%